Implementation of electronic prescription in a municipal public hospital (Research, Society and Development, 2023)
The aim of this study was to analyze the migration from manual prescriptions to the electronic model being implemented in a large municipal hospital in Rio de Janeiro. The work was divided into two parts: mapping processes with the activities carried out in the institution for the internal dispensing of medicines, and analyzing and comparing the time in the prescription screening process in the handwritten model with the electronic model in the process of implementation. The process mapping was elaborated after the implementation of the electronic medical record for a clinic, with the objective of standardizing the use of the system and observing the possible points of improvement. Comparing the screening time for manual and electronic prescriptions, 1,420 manual and 1,642 electronic prescriptions were analyzed from March to April 2021. The evidence found indicates that there is real potential for improvement with the adoption of the electronic patient record system, more specifically the electronic prescription, which will become more noticeable as the process is expanded to other clinics, until it covers all sectors of the hospital. However, it is essential to pay attention to the aspects of improvement found, in order to optimize the implementation process and the results sought, also ensuring better use of the investments made.